Ibn Sina's Concept of Thought About Education the Concept of Ibn Sina's Thoughts on Education - Nahdatul Hazmi; Jamaris; Sulfyarma M (International Journal of Educational and Life Sciences, 2024)
Ibnu Sina is a prominent figure in the Islamic world whose influence extends widely, not only in the Islamic world but also in the West. His expertise spans various fields, including medicine, philosophy, Islamic law, and education. Thus, it is an interesting study to explore Ibn Sina's conceptual thoughts on education. In the present time, there has been a decline in moral values across various groups, particularly among students. A simplistic view prevailing in society attributes the moral, ethical, and behavioral degradation of students to the failure of religious education in schools. It must be acknowledged that, to some extent, religious education does have certain weaknesses, ranging from minimal instructional hours, overly theoretical content, to educational approaches that tend to focus on the cognitive aspects rather than the affective and psychomotor aspects of students.